To produce the activated carbon from matured palm kernel shell - Zarifah Nadiah, Mohamad Salleh (2010)
The objectives of this experiment were to prepare the activated carbon from matured palm kernel shell as a raw material by carbonization and the studied which optimum variables such as temperature, concentration of phosphoric acid and cooling down time are suitable. Activated carbon is a form of carbon that has been processed to make extremely porous and have very large surface area for adsorption and chemical reactions. The matured palm kernel shell is carbonized in a glass furnace at elevation temperature after soaked with H acid and cooled down the carbonized activated carbon. Methyl orange are used as an indicator to test the carbonized raw material whether it is activated carbon or common charcoal. The real activated carbon would change the orange solution to a clear solution and the solution of different color is analyzed by using FTIR to check the functional group of methyl orange. The result showed that 1000